YOUNG ENTREPRENEURS’ CAPACITY FOR PUBLIC POLICY ADVOCACY IN MACEDONIA - Borota Popovska, M., Zabijakin Chatleska, V., and Topuzovska latkovikj, M. (University of “St. Kliment Ohridski” Bitola, 2016)
Existing literature argues that public policies affect entrepreneurship development by shaping economic, social and cultural factors. This is especially important for young entrepreneurs because they need a well developed structure of opportunities. Public policy advocacy in policy making processes can be useful and it can produce positive outcomes for both young entrepreneurs and policy makers. Starting from the basic assumption that policy advocacy can influence the creation and adoption of public policy decisions, this paper investigates the perceptions and attitudes of young entrepreneurs about the capacity for establishing advocacy organization. The presented study aims to identify several aspects of young entrepreneurs’ capacity for public policy advocacy: 1) perceived need for advocacy; 2) readiness for personal engagement in advocacy organization and 3) perceived barriers to effective advocacy. The research has been conducted at national level from different regions in the country. Online survey was administered to a purposive sample of young entrepreneurs from all ethnic groups. Research data were analyzed applying statistical techniques. Univariate and bivariate analysis were used. The results revealed that young entrepreneurs expressed a need for policy advocacy. They believe they can offer innovative solutions and consider it necessary to participate in creation of public policies that affect them. Moreover, readiness for engagement in advocacy organization positively correlates with the level of knowledge, skills and abilities for policy advocacy. The contribution of this paper is twofold. First, as is familiar to the authors, this is the first research of this kind in Macedonia. Second, it fills a gap in the study of youth entrepreneurship, particularly the study of young entrepreneurs’ policy advocacy and thus encourages more focused academic and public attention to this topic.
Keywords: young entrepreneurs; public policy advocacy; capacity for advocacy; Republic of Macedonia